PENGARUH KEMUDAHAN PENGGUNAAN, KENIKMATAN BERBELANJA, PENGALAMAN BERBELANJA DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI KONSUMEN DI SITUS JUAL BELI ONLINE BUKALAPAK.COM - Nurrahmanto, Prasetyo Agus; Rahardja, Rahardja (Diponegoro Journal of Management, 2015)
The advent of internet technology makes trading activities had been developed. Many businesses are using the nternet to conduct commerce, the new emerging business is an electronic commerce (e-commerce). One of the e-commerce that are emerging today is a consumer-to-consumer e-commerce, businesses create a new c2c e-commerce company based called the shopping website. With the shopping website, consumers no longer need to come to a conventional store to get the products they want. The purpose of this research is to know how the influence of the ease of use, shopping enjoyment, purchase experience and consumer trust towards consumer purchase intention on the Bukalapak.com shopping website.The sample in this research were internet users in Indonesia with a minimum age of 17 years who already shop one time on the Bukalapak.com shopping website or other sites, have a device with internet connectivity and bank account to make payments. The samples were 100 people selected using purposive sampling through an online questionnaire. Analysis of the data used in this research are descriptive analysis, multiple linear regression analysis and goodness of fit test.The results of the multiple linear regression analysis is, Y = 0,282 X1 + X2 + 0.098 0.292 + 0.270 X3 X4. The most influential independent variable towards the dependent variable is shopping enjoyment (0.292), followed by ease of use (0,282), consumer trust (0,270) and the last one is purchase experience (0.098). T test results showed that the ease of use, shopping enjoyment, purchase experience, and consumer trust variables have a positive and significant influence towards purchase intention, while the purchase experience variable have a positive and not significant influence towards purchase intention. The coefficient of determination obtained from the independent variable in this research is 63.8%, while the remaining 36,2% is influenced by other variables outside the model of this research.